Privação social como conceito de análise da pobreza urbana: horizontes teórico-conceituais para a geografia brasileira - Spode, Pedro Leonardo Cezar (2024)
Poverty is a complex social issue that is challenging to define. Throughout the 20th century, social sciences, including Geography, employed various concepts to study poverty, such as segregation, exclusion, marginalization, and more recently, vulnerability. However, there has been limited exploration in Brazilian Geography of social deprivation as a concept for analyzing poverty, particularly urban poverty. This research aims to fill this gap by focusing on the theoretical and conceptual reflection on social deprivation and its potential in analyzing urban poverty. The general objective is to discuss social deprivation as an analytical concept for urban poverty within the field of Geography. The study focuses on the urban area of the medium-sized city of Santa Maria, Rio Grande do Sul, Brazil. The method employed is historical-dialectical materialism, supported by concepts and analytical categories such as geographical space, used territory, territorial configuration, roughness, spaces of abundance and scarcity. Methodological procedures involve the operationalization of primary and secondary data collected through fieldwork, as well as data obtained from municipal departments of social development, housing, and planning in Santa Maria. Additionally, data from the Social Deprivation Index (SDI), developed from IBGE (2010) variables, are used for the urban area of Santa Maria. It was observed that social deprivation is concentrated in peripheral areas associated with specific features, such as railway structures, urban rivers, and hills. The spatial distribution of CadÚnico in Santa Maria's urban neighborhoods overlaps with the SDI layout, revealing discontinuous patches of poverty across the territory, particularly in peripheral areas. This territorial reality of poverty led to the identification of seven fragments of scarcity, where land uses are uneven and conditioned by different deprivation situations. These urban poverty fragments were termed highly deprived popular peripheries. It was observed that social deprivation allows for the analysis of urban poverty through two interrelated dimensions: on one hand, examining the multiple deprivations faced by groups in cities; on the other, identifying situations of resistance occurring in highly deprived popular peripheries.